O PIBID como elemento formativo e as concepções pedagógicas: um estudo a partir das percepções dos participantes de um subprojeto de biologia - Silva, Yara Rosa Romanelli Campos Gonçalves da (Universidade Federal de São Carlos, 2023)
The research has as general objective to investigate, through the perceptions of its participants, the Institutional Program of Scholarships for Initiation to Teaching (PIBID) – Biology as a formative element of science and biology teachers, from the pedagogical conceptions. The specific objectives are: to understand how the coordinators, students and references identify the PIBID - Biology as a formative element for future teachers of science and biology; investigate which pedagogical conceptions can be perceived in PIBID – Biology and to understand how these conceptions can influence the formative process and to analyze how the participants understand the activities promoted by PIBID Biology as formative elements, from the pedagogical conceptions that seem to underlie them. The research with a qualitative approach was based on carefully describing its methodological processes through a high scientific rigor of the data. These data came from a semi-structured interview, documentary analysis, bibliographic analysis and application of an online questionnaire. To understand and discuss the data, we used content analysis along with categorization, where this was analyzed in the light of the theoretical framework and the perceptions that could be inferred. The categories discussed are, respectively: PIBID as a formative element; Pedagogical conceptions and formative activities carried out in PIBID and pedagogical conceptions. Thus, when seeking to understand how the PIBID can be a formative element for teachers, understanding this issue through the pedagogical conceptions underlying it, we can conclude that the PIBID It is a very important formative space, being a promising program regarding the qualification of teacher learning in teacher training courses, because it puts students in direct contact with the practice of teachers, charging them to assume and perform attributions and actions jointly with peers and thus, forming a teacher. In addition, we understand that the presence of the conceptions that guide the teaching practice of teachers may be present in PIBID – Biology from the approaches classified by the author Mizukami herself (1986), this being the traditional, humanist, cognitivist, behaviorist and socio-cultural, the latter being the most noticeable according to the data. Thus, it is through the characteristics of these conceptions that the activities that the project proposes are built and can thus contribute to the understanding and constitution of the conceptions of the future teacher.
The PIBID as a formative element and the pedagogical conceptions: a study to from the perceptions of the participants of a biology subproject
Keywords: Formação de professores; PIBID; Concepções pedagógicas; Espaços formativos; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO